Implementasi Penggunaan Model Project Based Learning (PJBL) Dalam Pembuatan Pestisida Organik Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa - Danang Margono; Asep Ginanjar Arip; Anna Fitri Hindriana (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2018)
Research objectives analyze the feasibility, increase creativity, learning outcomes and student responses to project based learning (PjBL) learning models in making organic pesticides. The results of the study was found that: The PjBL model of making organic pesticides can develop students' creativity. The results of the significance hypothesis test 0,004<0.05, the initial hypothesis (Ho) is rejected, meaning that there is a difference in the average creativity of students between the experimental class and the control class. The results of the hypothesis test of learning outcomes obtained sig values. 0,000 <0,05 then the initial hypothesis (Ho) is rejected indicating that there are differences in cognitive learning outcomes between the experimental class and the control classKeywords: Project Based Learning (PjBL); Pestisida Organik; Kreativitas